Acoustic frequency comb generation on a composite diamond/silicon microcantilever in ambient air - Zhixin Zhao; Yanyan Li; Wangyang Zhang; Wenyao Luo; Duo Liu (Microsystems & Nanoengineering)
Abstract Acoustic frequency combs (AFCs) contain equidistant coherent signals with unconventional possibilities on metrology. Previously, implementation of AFCs on mechanical microresonators with large air damping loss is difficult, which restricted their atmospheric applications. In this work, we explore the potentials of a composite diamond/silicon microcantilever for parametric generation of AFCs in ambient air. We discover that the diamond layer provides a viable route to reduce the linewidth of the primary flexural mode, yielding a 7.1-times increase of the quality factor. We develop a parametric driving scheme that enables generation of AFCs through injection locking and sequential nonlinear dynamic transitions involving subharmonic synchronization (Arnold tongue), and chaotic dynamics. Ultimately, we realize AFCs with a frequency range extending 800 kHz in the air. This work advances the understanding of AFCs and provides a viable route towards their applications in ambient air for high precision metrology.